Distribution of ABO and Rhesus (Rh) Blood Groups among Voluntary Donors in Kachchh Gujarat (GAIMS Journal of Medical Sciences, 2025)
Background: The ABO and Rh blood group systems are the most important blood group systems in Transfusion Medicine. This study was carried out with an objective to study the distribution of ABO and Rh blood groups among voluntary blood donors in Western Gujarat, India which is essential for effective management of blood inventory.Material and methods: The present retrospective study was carried out at GKGH Blood centre. The data of present study is from 01/01/2024 TO 31/12/2024. Total 19355 voluntary blood donors were considered medically fit and accepted for blood donation. ABO and Rh typing were done by Complete Grouping Card method by Tulip matrix, both forward and reverse blood grouping after validation at blood centre.    Results: Out of 11,013 blood donors O blood group was most common (3520-31.96%) and the least blood group was AB Blood group (70-0.63%). There were more Rh-Positive blood donors as compared to Rh Negative blood donors.   Conclusion: The most common blood group among voluntary donors was O positive and least common blood group was AB negative.